Data governance in der wissenschaftlichen Literatur: Eine Begriffsklärung anhand einer Text-Mining-basierten Literaturrecherche; Data governance: A definition of terms using a text-mining-based literature review - Alevtina Krotova; Jan Eppelsheimer (IW-Trends - Vierteljahresschrift zur empirischen Wirtschaftsforschung, 2019)
Data governance forms the basis of efficient data management within companies and across company boundaries. In practice, however, there is no clear and uniform definition of data governance and its components. In order to provide a comprehensive overview of data governance, to reveal previous research trends and to uncover potential research needs, a text-mining-based systematic literature review was conducted. With this method the authors established that the place occupied by data governance in scientific debate and literature has been constantly growing, especially since 2012. They identified a total of nine clusters, each representing an existing research priority. The analysis revealed that the main topic of data governance research is its significance for digital technologies. Further aspects of data governance addressed in the literature include use of data as an economic asset, data management, data quality, data protection, compliance and organisation of data in networks. Data governance already plays a more important role in the health sector than in other industries. By effectively coordinating the requirements of business practice and scientific problem analysis, data governance can be better investigated, developed and implemented. – – The proposed universal basic pension (Grundrente) is intended to acknowledge the contribution to society made by indigent pensioners during their working lives. However, a higher pension without a means test would in four cases out of five mean misdirecting aid to those not in need. Even in cases where the current statutory pension entitlement is lower than the entitlement to basic provision (Grundsicherung), as part of a combined household income the pension still usually succeeds in averting old age poverty. It would therefore make more sense to deduct a personal allowance from the means test, irrespective of the type of income involved. An allowance of up to 200 euros per month would benefit almost all those originally identified as potentially needing assistance if they simultaneously claimed basic provision. However, this would involve the needy being treated differently depending on their individual income in old age. Alternatively, to avoid this unequal treatment, the standard rates of old-age basic provision could be raised for all indigent pensioners. While it would raise the number of potential beneficiaries, this should be interpreted less as an alarm signal than as an indication of an effective old-age pension system. To increase acceptance of income support as part of Germany's social security architecture, the means test needs to be designed to appear less humiliating.
Keywords: L14; L15; O30; 330; Data Economy; Data Governance; Clusteranalyse